ISLAMIC ECONOMIC TRANSFORMATION IN THE DIGITAL ERA: A REVIEW OF THE ROLE OF FINTECH - atikah, nila; Widya Astuti , Aurelia; Sayudin, Sayudin; Khan, Aisha; Hussain, Syed Araick; Umar, Manir (Jurnal Impresi Indonesia, 2023)
This research examines the transformation of the sharia economy in the digital era with a focus on the role of Financial Technology (Fintech). Advances in information and communication technology have had a significant impact on the structure of the global economy, including Islamic financial practices. Fintech as a digital financial innovation has the potential to accelerate the growth of the sharia financial sector. This research uses a qualitative approach to analyze Fintech developments in the context of Islamic economics. Data collection was carried out through literature studies and interviews with financial practitioners and Islamic economics experts. It is hoped that the results of this research will provide an in-depth understanding of the impact of Fintech on the sharia financial ecosystem and how this innovation can strengthen sharia economic principles. In the digital era, the transformation of the sharia economy through fintech has brought significant changes, opening up financial access for Muslim communities who were previously marginalized in the conventional financial system.